Relationship between Hypothyroidism and Non-Alcoholic Fatty Liver Disease: A Systematic Review and Meta-analysis - He, Weiwei; An, Xiaofei; Li, Ling; Shao, Xiaoqing; Li, Qian; Yao, Qiuming; Zhang, Jin-an (Frontiers in Endocrinology, 2017)
Background: Previous studies propose that hypothyroidism might play a crucial role in the pathogenesis of non-alcoholic fatty liver disease (NAFLD), but findings from published studies on the relationship between hypothyroidism and NAFLD are still controversial. Our study aimed to make a comprehensive evaluation of the relationship between hypothyroidism and NAFLD through a meta-analysis. Methods: PubMed, China Dissertation Database, and EMBASE databases were searched to find observational studies assessing the relationship between hypothyroidism and NAFLD. The pooled odds ratios (ORs) with 95% confidence intervals (95%CIs) were calculated to evaluate the strength of the relationship between hypothyroidism and NAFLD through meta-analysis. Results: Thirteen articles were ultimately included in our meta-analysis. Meta-analysis of the 13 studies found a high correlation between hypothyroidism and NAFLD (OR = 1.52, 95%CI 1.24-1.87, P <0.001). Meta-analysis of 9 studies providing adjusted ORs found that hypothyroidism was independently correlated with NAFLD (OR = 1.72, 95%CI 1.32-2.23, P <0.001). Subgroup analysis found that both overt hypothyroidism and subclinical hypothyroidism were significantly correlated with NAFLD, and the pooled ORs were 1.70 (95%CI 1.23-2.36, P = 0.002) and 1.40 (95%CI 1.10-1.77, P = 0.006), respectively. Besides, meta-analysis of studies providing adjusted ORs also found that both overt hypothyroidism and subclinical hypothyroidism were independently correlated with NAFLD, and the pooled ORs were 1.81 (95%CI 1.30-2.52, P <0.001) and 1.63 (95%CI 1.19-2.24, P = 0.002), respectively. Conclusion: The meta-analysis provides strong epidemiological evidence for the relationship between hypothyroidism and NAFLD. Both individuals with subclinical and overt hypothyroidism are at higher risk for NAFLD than euthyroid subjects.